PROTECTION ON CULTURAL EXPRESSION AS A COPYRIGHTS OF THE KAKULA TRADITIONAL MUSIC - Korompot, Ratu Ratna; Miqat, Nurul (Tadulako Law Review, 2016)
Legal instruments that can be used to protect music Kakula as traditional cultural heritage namely Intellectual Property Rights, in this case the rules relating to Copyright can be used as a basis for the protection of traditional musical art music Kakula. Copyright law provisions can be used as a basis for protecting cultural works are included in the scope of knowledge of art and literature. Kakula is a traditional musical instrument which is the traditional cultural heritage which is always used at events such as marriage ritual, the coronation of noble titles or formal occasions regions. The approach method in use is normative and normative anthropology, which takes secondary data and primary data through interviews with the parties relating to the cultural resources in the city of Palu, Donggala, and Sigi. As a result of the research after proposed in 2015, in 2016 coincided Kakula has been proposed to register as one of the Objects of Folklore.